STN ISO 579: 2002 (44 1384), Koks. Stanovenie celkového obsahu vody. - Kóciová, Gabriela; Krejčík, Zdeněk; Tyle, Pavel (Slovenský ústav technickej normalizácie, 2002)
Táto norma obsahuje ISO 579: 1999 v českom jazyku